Age, creatinine, and ejection fraction score is a risk factor for acute kidney injury after surgical aortic valve replacement - Tingting Wu; Rui Li; Jing Chen; Xiaqiu Tian; Ran Zhang; Xiaotong Hou (Renal Failure)
Background The incidence of acute kidney injury (AKI) increases after surgical aortic valve replacement (SAVR). This study aimed to characterize the risk factors of AKI after SAVR.Methods and Results We conducted a retrospective registry study based on data from 299 consecutive patients undergoing SAVR. At 48 h after SAVR, 41 patients developed AKI. There was a significantly higher prevalence of older age, higher body mass index (BMI), and diabetes mellitus in the AKI group. Previous use of angiotensin-converting enzyme inhibitors/angiotensin receptor blocker (ACEI/ARB) and β-blocker, intake and output volumes within 24 h, mechanical ventilation time, length of intensive care unit and hospital stay, baseline creatinine, baseline, 24 h, and 48 h estimated glomerular filtration rate were strongly associated with the incidence of AKI. BMI >24, history of hypertension, use of ACEI/ARB and β-blocker, and mechanical ventilation time were associated with AKI. Univariate logistic regression indicated that overweight, hypertension, use of ACEI/ARB and β-blocker, and mechanical ventilation time were associated with AKI. Notably, the ACEF score was an independent predictor of AKI. The receiver operating characteristic curve was employed to assess the ACEF score for predicting AKI and the best cutoff was 1.1. After dividing ACEF into quartiles, each one-unit increment in ACEF led to a 2.27-fold risk in the incidence of AKI among patients.Conclusions AKI is a generalizable phenomenon occurring frequently after SAVR. The ACEF score is an independent predictor of AKI among patients undergoing SAVR.